The Influence of Gender Ideology, Victim Resistance, and Spiking a Drink on Acquaintance Rape Attributions. Issue 20 (October 2018) - Angelone, D. J.; Mitchell, Damon; Smith, Danielle
The current study examined observer's attributions about the victim and perpetrator of an alleged acquaintance rape. Participants included 504 college students from a public university in the northeastern United States who read a brief crime report and completed a series of questionnaires for course credit. While men tended to attribute more blame to the victim than women, gender ideology emerged as a stronger predictor of rape attributions, and some types of sexist beliefs were associated with greater victim blaming and others with less victim blaming. Endorsement of hostile sexism, rape myths, and heterosexual intimacy was generally associated with the attribution of greater victim culpability, as well as less perpetrator culpability, perpetrator criminality, and victim credibility. However, complementary gender differentiation was associated with greater perpetrator culpability and criminality, while protective paternalism was associated with greater victim credibility. Observers attributed lower victim culpability and greater perpetrator criminality when the victim's drink was spiked, and attributed greater perpetrator culpability when the victim verbally resisted the perpetrator's advances. Given the implications that observer attitudes can have on professional and personal support for survivors, as well as juror decision making, the ongoing examination of the complex interplay between the person and situational factors affecting attributions of rape is essential. Sexual assault prevention programs may also benefit from a psychoeducational component that targets reducing traditional gender ideology.